Numerical Investigation and Design of Reinforced Concrete Shear Wall Equipped with Tuned Liquid Multiple Columns Dampers - Zhe Wang; Liang Cao; Filippo Ubertini; Simon Laflamme (Shock and Vibration)
The tuned liquid multiple column damper (TLMCD) is a variation of the tuned liquid column damper (TLCD) that includes multiple vertical columns. A new damping system that embeds TLMCDs within reinforced concrete shear wall systems, termed tuned liquid wall damper (TLWD), is proposed, augmenting the traditional structural component with energy dissipation capabilities. The objective of this study is to assess energy mitigation and strength trade-offs in designing TLWDs and demonstrating the promise of TLWD systems in tall buildings through vertically distributed applications. This is done by investigating the performance of the proposed TLWD through the finite element model (FEM) of a simplified representation of a 42-story building equipped with the multifunctional component. A strength model for the TLWD is developed to empower faster performance evaluation on more complex models. Results from the FEM are used to validate the strength model and show that the model could be used conservatively in assessing strength performance. Design considerations are discussed based on the simplified representation. In particular, to improve mitigation performance while maintaining strength, it is found that a single-layer arrangement of the vertical columns is preferred, while distributing the inertia among a higher number of smaller columns. The proposed TLWD is numerically evaluated on a more realistic system consisting of a multi-degrees-of-freedom representation of the 42-story building under stochastic wind excitation. Simulation results demonstrate that the TLWD, used in a vertically distributed configuration through the building, could be used to mitigate vibrations, outperforming a traditional TLCD system with geometric constraints under 20 design wind realization. Results from the numerical simulations also confirmed the design considerations established through the simplified representation.